A Generalised Coordination Design Pattern for the EX-MAN Component Model - Tauseef Rana; Abdullah Baz (IEEE Access, 2020)
In the latest technologies for next generation using in Cyber-Physical Systems, 5G and IoT (Internet of Things) based solutions have a significant contribution. For the construction of such applications, component-based development approaches offer to produce systems by using pre-built tested and reliable components with shorter development time. At the architecture level, a software system can be viewed as a collection of two kinds of elements. One kind is responsible for computation and the other kind is responsible for communication. Using a component model, that separates the communication and computation into distinct layers, enables us to secure the communication part of the system. In this paper, we propose a design pattern which defines coordination/communication program units (referred to as exogenous connectors) for a repository of reusable connectors in the EX-MAN component model. There are many attempts of implementing exogenous connector in different tools in unspecified ways. Our proposed pattern for a generalised exogenous connector helps in specifying exogenous connectors with enough details that can be used for the implementation of these connectors. Our model enables in-depth analysis of different kinds of exogenous connectors with respect to its static/dynamic behaviour in a system. In this paper, we model and simulate the static/dynamic behaviour of sample exogenous connectors based on our proposed model. Using our specifications of exogenous connector, we have developed exogenous composition framework (ECF) for system development.